2008
DOI: 10.1111/j.1751-7915.2008.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of twin‐arginine translocation for expression and purification of correctly folded proteins in Escherichia coli

Abstract: SummaryHistorically, the general secretory (Sec) pathway of Gram‐negative bacteria has served as the primary route by which heterologous proteins are delivered to the periplasm in numerous expression and engineering applications. Here we have systematically examined the twin‐arginine translocation (Tat) pathway as an alternative, and possibly advantageous, secretion pathway for heterologous proteins. Overall, we found that: (i) export efficiency and periplasmic yield of a model substrate were affected by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 70 publications
(173 reference statements)
2
28
0
Order By: Relevance
“…The molecular mass of this band was just under 50 kDa, which likely corresponds to tetraglycosylated AcrA-4ϫ (44.2 kDa) that has retained its Nterminal spTorA signal peptide (4.2 kDa). Indeed, it has been observed that overexpression of Tat substrates and cell stress negatively affect the efficiency of signal peptide removal in E. coli (19,54). Based on the slow electrophoretic mobility of this protein and its analysis by nanoLC-MS/MS, which revealed N-linked glycosylation at all four sites (data not shown), we conclude that tetraglycosylated AcrA-4ϫ is the predominant glycosylated species produced by the Tat pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mass of this band was just under 50 kDa, which likely corresponds to tetraglycosylated AcrA-4ϫ (44.2 kDa) that has retained its Nterminal spTorA signal peptide (4.2 kDa). Indeed, it has been observed that overexpression of Tat substrates and cell stress negatively affect the efficiency of signal peptide removal in E. coli (19,54). Based on the slow electrophoretic mobility of this protein and its analysis by nanoLC-MS/MS, which revealed N-linked glycosylation at all four sites (data not shown), we conclude that tetraglycosylated AcrA-4ϫ is the predominant glycosylated species produced by the Tat pathway.…”
Section: Resultsmentioning
confidence: 99%
“…a large scale. It transports folded proteins across the plasma membrane, and even appears to preferentially transport correctly folded proteins [5,6]. It may therefore be particularly advantageous for the export of Secincompatible proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the Tat system translocates fully folded proteins, and it thus differs in fundamental respects from the Sec pathway. The system has been shown to be able to transport a variety of heterologous proteins [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of MBP, after formation of an ssTorA-X::Y-MBP complex, MBP must bind maltose and then deliver it to the MalFGK(2) inner membrane complex. The intricacy of this reporter activity may prove problematic, especially considering that, in certain instances, direct fusions to MBP (e.g., ssTorA-GFP-MBP) are incapable of performing this function even when the fusion protein is correctly localized to the periplasm and the fusion partner (e.g., GFP) is active (52). It should also be pointed out that even though previous reports suggest Bla is undesirable as a reporter because low-level resistance to Amp has been observed with Bla lacking a signal peptide (33,51), in our hands, we never observed nonspecific leakage of Bla to the periplasm (Fig.…”
Section: Discussionmentioning
confidence: 99%